2008
DOI: 10.1524/jbwg.2008.49.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Zahlenfähigkeit und Zahlendisziplin in Nord- und Westdeutschland, 16.-18. Jahrhundert

Abstract: Die Europäer genießen ohne Zweifel einen sehr viel höheren Lebensstandard als die Bewohner anderer Erdteile, wie z.B. Afrika oder Asien. Als wichtigste Gründe gelten beim derzeitigen Stand der Forschung vor allem institutionelle Entwicklungen zwischen Mittelalter und der Zeit um 1800. Die frühe Entwicklung einklagbarer Verträge, der Buchführung oder die Schaffung von Börsen führten in Europa und der europäisch besiedelten Neuen Welt zu einem Entwicklungsvorteil gegenüber anderen Weltregionen, der im 19. und 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Age heaping has been used a number of times recently to measure education levels (Mokyr, 1983;2008b;A'Hearn, Baten and Crayen, 2009;de Moor and van Zanden, 2008;Clark, 2007;Manzel, 2007;Baten, Crayen and Manzel, 2008, see also the applications in Cinnirella, 2008;Mironov, 2006;. It describes the phenomenon that people tend to round up or down their age, mostly in multiples of five, when asked how old they are.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Age heaping has been used a number of times recently to measure education levels (Mokyr, 1983;2008b;A'Hearn, Baten and Crayen, 2009;de Moor and van Zanden, 2008;Clark, 2007;Manzel, 2007;Baten, Crayen and Manzel, 2008, see also the applications in Cinnirella, 2008;Mironov, 2006;. It describes the phenomenon that people tend to round up or down their age, mostly in multiples of five, when asked how old they are.…”
Section: Methodsmentioning
confidence: 99%
“…The degree to which age heaping is influenced by schooling and the effect of other institutional factors is not easy to disentangle, although Crayen and Baten (2008) assessed this and found that schooling was more important than other factors such as bureaucracy and previous census-taking. We conclude…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… A'Hearn, Baten, and Crayen, ‘Quantifying quantitative literacy’; Baten, Crayen, and Manzel, ‘Zahlendisziplin’; De Moor and van Zanden, ‘ “Leeftijdstapelen” ’; Clark, Farewell to alms , pp. 175–81; Crayen and Baten,‘Global trends in numeracy’; Manzel and Baten, ‘Gender equality’; Cinnirella, ‘Nutritional status’; Mironov, ‘Novaya istoricheskaya demografia’; Ó Gráda, ‘Dublin Jewish demography’. …”
mentioning
confidence: 99%
“…Since 1922, ethnic German immigrants to this region were subsumed under the term ‘Danube Swabians’ ( Donauschwaben ). Sources : Germany: A’Hearn et al., ‘Quantifying quantitative literacy’; Baten, Crayen, and Manzel, ‘Zahlenfähigkeit und Zahlendisziplin’. ‘Danube Swabians’: unpublished data provided by Zoltán Csapo.…”
Section: Historical Background and Data Sourcesmentioning
confidence: 99%